Hanging Out, Messing Around, and Geeking Out : Kids Living and Learning with New Media - Ito, Mizuko; Baumer, Sonja; Bittanti, Matteo; boyd, danah; Cody, Rachel; Stephenson, Becky Herr; Horst, Heather A.; Lange, Patricia G.; Mahendran, Dilan; Martínez, Katynka Z.; Pascoe, C. J.; Perkel, Dan; et al. (Cambridge The MIT Press, 2010)
An examination of young people's everyday new media practices including video-game playing, text-messaging, digital media production, and social media use. Conventional wisdom about young people's use of digital technology often equates generational identity with technology identity: today's teens seem constantly plugged in to video games, social networking sites, and text messaging. Yet there is little actual research that investigates the intricate dynamics of youths' social and recreational use of digital media. Hanging Out, Messing Around, and Geeking Out fills this gap, reporting on an ambitious three-year ethnographic investigation into how young people are living and learning with new media in varied settings at home, in after-school programs, and in online spaces. Integrating twenty-three case studies which include Harry Potter podcasting, video-game playing, music sharing, and online romantic breakups in a unique collaborative authorship style,Hanging Out, Messing Around, and Geeking Out is distinctive for its combination of in-depth description of specific group dynamics with conceptual analysis.
English
Keywords: Impact of science & technology on society; Educational equipment & technology, computer-aided learning (CAL); social media; youth media; children's media; podcast; video-games; videogame; text message; ethnography; Digital Youth Project; media literacymedia ecology